Evaluasi Struktur Ginjal dan Eritrogram Itik Hibrida Setelah Pemberian Imbuhan Pakan Tepung Daun Kelor (Moringa oleifera Lam.) - Kasiyati, Kasiyati; El Fahmi, Ribki (Jurnal Sain Veteriner, 2025)
Feeding hybrid ducks with low nutritional quality may cause growth and health disorders, such as changes in the kidney structure and erythrogram. Moringa leaf meal contained antioxidants and nutrients that had the potential to be used as a feed supplement to support the growth and health of hybrid ducks. The aim of this study was to evaluate feed inclusion of moringa leaf meal on the kidney structure and erythrogram of hybrid ducks. This study used a Completely Randomized Design (CRD) consisting of 4 treatments, including K0 (feed without moringa leaf meal), K1, K2, and K3 were feed treatments with the addition of 2.5%, 5%, and 7.5% moringa leaf meal, respectively, each repeated 6 times. The measured variables of kidney structure included renal corpuscle diameter, renal corpuscle density, proximal tubule diameter, and distal tubule diameter. Erythrogram variables included erythrocytes, hemoglobin, hematocrit, MCV, MCH, and MCHC. Data were tested and analyzed using ANOVA with a 5% significance level. The study results showed that moringa leaf meal supplements had no effect   (P > 0.05) on the kidney microstructure and erythrogram of hybrid ducks. The conclusion of this study was that moringa leaf meal supplements had the potential to maintain kidney structure and erythrogram, thus ensuring the healthy physiological status of ducks.